Model Struktural Kinerja Pegawai: Peran Kepuasan Dalam Memediasi Workplace Friendship, dan Interpersonal Trust - Siddik Ega; Hutasuhut Julianto; Rahmat Muhammad; Sihite Frans Antoni (Forum Kerjasama Pendidikan Tinggi, 2026)
This study aims to analyze the effect of workplace friendship and interpersonal trust on employee performance with job satisfaction as a mediating variable at the Food Crops and Horticulture Service of North Sumatra Province. This study uses a quantitative approach with an explanatory research design on 62 samples of employees of the Food Crops and Horticulture Service of North Sumatra Province selected by the Slovin formula and proportional stratified random sampling technique. Data were collected through a valid and reliable 5-point Likert scale questionnaire, then analyzed using SEM-PLS with SmartPLS 3.0 software. The results showed that interpersonal trust had a significant positive effect on employee satisfaction and performance, temporary friendship at work also had a positive effect on satisfaction and performance although with a smaller direct effect. In addition, job satisfaction had the strongest influence on employee performance and acted as a significant mediator in the relationship between interpersonal trust and workplace friendship with performance.